Measures of Population Ageing in Terms of the Potential Approach – Analysis Based on the Example of Poland - Adrianowska, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
The article presents the proposals for population aging rates defined from the perspective of potential demography – in a static and dynamic perspective. It also presents the method of calculating life potentials for the population and for individual age groups, which are the starting point in potential demography. The values of the population aging rates in terms of the concepts of potential demography were calculated for Poland as a case study.